Rural Development Centers (Farm Stores) in Afghanistan, Do they work? The business owners' perspectives - Tim Kock; Jerry Turnbull (Journal of International Agricultural and Extension Education, 2011)
Afghanistan is as country yearning for development and the agricultural sector needs to lead the way. The need for agricultural based businesses was evident throughout the country, rural areas depended businesses that could supply the needed inputs required in agricultural production. This experimental case study describes the yearlong results the USAID funded VEGA P2K development program, the program designed and implemented 12 rural development centers (farm stores) built in Afghanistan during 2009. These businesses provided inputs, credit, wholesaler markets, equipment rental and extension services to farmers. Business owners indicated that all of the aspects of the stores were beneficial to the rural people of Afghanistan.
Keywords: Afghanistan; agriculture; business development and extension